Предмет: Алгебра,
автор: natashenkakondr
помогите СРОЧНОООО ОЧЕНЬ НУЖНО
Приложения:
Ответы
Автор ответа:
0
√ (27 + 10√2) - √(27 -10√2) = √(25 +2 + 10√2) - √(25 +2 -10√2) =
=√(5² +(√2)² + 2*5*√2) - √(5² +(√2)² - 2*5*√2)=
=√(5 + √2)² - √(5 - √2)² = 5 +√2 - 5 + √2 = 2√2
=√(5² +(√2)² + 2*5*√2) - √(5² +(√2)² - 2*5*√2)=
=√(5 + √2)² - √(5 - √2)² = 5 +√2 - 5 + √2 = 2√2
Похожие вопросы
Предмет: Химия,
автор: angelinatimosenko276
Предмет: Английский язык,
автор: hhggggh
Предмет: Математика,
автор: AnnaGruber1011
Предмет: Математика,
автор: Леонид17
Предмет: История,
автор: eostrovsky